Pengaruh Teknik Relaksasi Benson Terhadap Kualitas Tidur pada Lanjut Usia - Hidayat, Rahmat; Amir, Haeril (An Idea Health Journal, 2021)
Benson Relaxation is a technique for reducing pain, overcoming sleep disorders and dealing with anxiety. The developmental stage of the elderly is characterized by the loss of a lot of body cells and a decrease in the metabolism of body cells which causes a decrease in body function and changes in body composition as well as a decrease in strength and health. One of the complaints that are felt related to sleep is difficulty sleeping, often waking up during the night and feeling unrefreshed wh en awakened from sleep.